The Relationship Between Midwive's Interpersonal Communication And Patient Satisfaction With Midwifery Services - Cut Mutiah; Rezqiqah Auliah Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Interpersonal communication is an important component in midwifery services because it plays a role in building a therapeutic relationship between midwives and patients. Effective communication can increase trust, comfort, and patient satisfaction with the services received. This study aims to determine the relationship between midwives' interpersonal communication and patient satisfaction with midwifery services. The research method used is quantitative research with a descriptive analytical design and a cross-sectional approach. The study sample consisted of 100 patients who received midwifery services at health facility X. Data collection was carried out using an interpersonal communication questionnaire and a patient satisfaction questionnaire. Data analysis was carried out using the chi-square test. The results showed a significant relationship between midwives' interpersonal communication and patient satisfaction (p < 0.05). The conclusion of this study is that the better the midwive's interpersonal communication, the higher the level of patient satisfaction with midwifery services.